Is the WTO dispute settlement procedure fair to developing countries? - Bouët, Antoine; Metivier, Jeanne (International Food Policy Research Institute, 2017)
Since the inception of the World Trade Organization (WTO) in 1995, member countries have been heavily relying on the organization's dispute settlement procedure (DSP). Exploiting a new database on WTO litigations between 1995 and 2014, this paper describes disputes initiated over this period and identifies potential sources of bias concerning the participation of developing countries. The analysis builds on three different models to determine country i's probability of initiating a dispute against country j. Either it depends only on the two countries' structure of trade, that is the number of products exported by i to j (a situation we refer to as the rules-based model), or it is also affected by country i's or country j's specific characteristics (the unilateral power-based model), or it is also affected by bilateral economic and trade relations between countries i and j (the bilateral power-based model). We find that country i's structure of trade with j plays an important role in explaining the probability that i initiates a dispute against j under the DSP. Furthermore, country i's legal capacity and both countries' political regimes also affect this probability. However, we do not find that bilateral relationships between i and j, such as participants' capacity to retaliate against each others have an impact on dispute initiation.